Sex and gender differences in access, quality of care, and effectiveness of treatment in dementia: a scoping review of studies up to 2024 - Elisa Aguzzoli; Magdalena Walbaum; Martin Knapp; Laura Castro-Aldrete; Antonella Santuccione Chadha; Eva Cyhlarova (Archives of Public Health)
Abstract Background Dementia represents one of the greatest global health challenges. Women have a greater lifetime risk of developing dementia compared to men. Both pharmacological and non-pharmacological interventions aimed at slowing cognitive decline show promising results. However, most studies do not examine whether there are sex and gender differences in access to treatment, quality of care or treatment effectiveness. Objectives To summarise evidence on sex and gender differences in access to treatment, management, and treatment effectiveness for people with dementia. Methods This scoping review followed PRISMA guidelines and was conducted in PubMed/MEDLINE, EMBASE, Google Scholar, and ClinicalTrials.Gov databases in November 2023 and updated in January 2024. Systematic reviews and observational studies were included to explore sex and gender differences in access or management of dementia. Systematic reviews and clinical trials were included to investigate sex and gender differences in treatment effectiveness. Results We included 16 studies in our review. Sex and gender differences were observed in the prescription and receipt of anti-dementia medications, as well as access to primary care, with variations by settings. Mixed results were found concerning polypharmacy and inappropriate medications, with women being prescribed antipsychotic and other psychotropic medications for longer periods compared to men. Studies of the impact of exercise on cognitive decline yielded mixed results, though limited disaggregated data by sex indicated a more pronounced impact in women than in men. Cognitive stimulation therapy interventions showed greater cognitive improvements for women. Clinical trials assessing the effectiveness of disease-modifying therapies (DMTs) suggest that women may be less responsive to DMTs than men. Conclusions There are important differences between men and women living with dementia in access to diagnosis, treatments, quality of care and effectiveness of treatments. Such differences can significantly impact health outcomes. Sex and gender inequalities should be considered when planning and implementing healthcare, social care, and associated strategies in dementia. To provide conclusive evidence, it is essential for clinical trials to have sufficient statistical power and report outcomes disaggregated by sex.